Physical and Biogeochemical Properties of Rotten East Antarctic Summer Sea Ice. Issue 2 (4th February 2023) - Corkill, M.; Moreau, S.; Janssens, J.; Fraser, A. D.; Heil, P.; Tison, J.‐L.; Cougnon, E. A.; Genovese, C.; Kimura, N.; Meiners, K. M.; Wongpan, P.; Lannuzel, D.
Abstract: Sea ice forms a barrier to the exchange of energy, gases, moisture and particles between the ocean and atmosphere around Antarctica. Ice temperature, salinity and the composition of ice crystals determine whether a particular slab of sea ice is habitable for microorganisms and permeable to exchanges between the ocean and atmosphere, allowing, for example, carbon dioxide (CO2 ) from the atmosphere to be absorbed or outgassed by the ocean. Spring sea ice can have high concentrations of algae and absorb atmospheric CO2 . In the summer of 2016–2017 off East Antarctica, we found decayed and porous granular ice layers in the interior of the ice column, which showed high algal pigment concentrations. The maximum chlorophyll a observed in the interior of the ice column was 67.7 μg/L in a 24% porous granular ice layer between 0.8 and 0.9 m depth in 1.7 m thick ice, compared to an overall mean sea‐ice chlorophyll a (± one standard deviation) of 13.5 ± 21.8 μg/L. We also found extensive surface melting, with instances of snow meltwater apparently percolating through the ice, as well as impermeable superimposed ice layers that had refrozen along with melt ponds on top of the ice. With future warming, the structures we describe here could occur earlier and/or become more persistent, meaning that sea ice would be more often characterized by patchy permeability and interior ice algal accumulations. Plain Language Summary: The growth and melt of Antarctic sea ice is one of the largest seasonal events on Earth. The rapid changes visible at its surface correspond to changes hidden inside the sea ice. East Antarctic sea‐ice samples were collected in 2016–2017 from the icebreaker RSV Aurora Australis to investigate the internal structure of sea ice in summer. Capping the sea ice, impermeable layers inhibited vertical transfer of material through the ice, but ponds had also melted through these layers to allow exchange between the ocean and atmosphere. We also found high concentrations of ice algae deep inside the sea ice, which might be inaccessible to grazers but important for absorbing atmospheric carbon dioxide. With warming temperatures, the observed ice characteristics may become more common or persist longer in each summer with potential consequences for ecosystem processes. Key Points: East Antarctic summer sea ice can be rotten, with melt ponds, but otherwise sealed by superimposed ice and mostly stratified brine Deep layers of decayed granular crystals allow infiltration of relatively nutrient‐rich seawater and sustain algal assemblages Evidence for incorporation of old pack ice floes into landfast sea ice